The influence of different gums compared with surfactants as encapsulating stabilizers on the thermal, storage, and low-pH stability of chlorophyllin - Hamed Hosseini; Vahid Pasban Noghabi; Hamed Saberian; Seid Mahdi Jafari (Food Chemistry: X, 2023)
Sodium copper chlorophyllin (SCC), with a higher stability and water solubility than chlorophyll, has limited applications in acidic products due to precipitation. We investigated the effect of pectin (PE), carboxymethyl cellulose (CMC), xanthan gum (XG), carrageenan gum (CG), gellan gum (GG), tragacanth gum (TG), gum Arabic (GA), and polysorbate 80 (PS80) on SCC stability in acidic model solutions (pH = 3.5). These stabilizers led to a significant reduction in particle size and zeta-potential compared to control sample. GA (33.3:1), PE (8:1), CMC (4:1), XG (1.33:1), and PS80 (0.67:1) stabilized SCC in acidic systems for 28 days. The FTIR analysis showed that mainly electrostatic and hydrogen bonds between SCC and stabilizers led to a substantial decline in particle size, improving SCC distribution and stability within acidic environment. Thus, XG and CMC could be effectively used for SCC stabilization under acidic solutions where applying PS80 surfactant is a health concern.